2014
DOI: 10.3390/molecules191220023
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Selected Dietary Secondary Metabolites on Reactive Oxygen Species Production Caused by Iron(II) Autoxidation

Abstract: Iron is an essential co-factor for many enzymes that catalyze electron transfer reactions. It is well known that so-called “poorly liganded” iron can increase ROS concentrations and trigger oxidative stress that is capable of initiating apoptosis. Conversely, controlled ROS production has been recognized as an integral part of cellular signaling. Elevated ROS concentrations are associated with aging, inflammatory and degenerative diseases. Anti-aging properties have been attributed especially to antioxidant ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
2

Year Published

2015
2015
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 66 publications
1
26
0
2
Order By: Relevance
“…Evidences has shown that there is a significant increase in ROS production with an increase in amount of Fe ions which in turn leads to more cellular toxicity effects [61,62]. Our results demonstrated that the cytotoxicity of these nanoparticles enhanced with increasing the Fe 3 O 4 concentration.…”
Section: Discussionsupporting
confidence: 58%
“…Evidences has shown that there is a significant increase in ROS production with an increase in amount of Fe ions which in turn leads to more cellular toxicity effects [61,62]. Our results demonstrated that the cytotoxicity of these nanoparticles enhanced with increasing the Fe 3 O 4 concentration.…”
Section: Discussionsupporting
confidence: 58%
“…At the higher investigated concentration, the aqueous extract showed an outstanding activity and restored the GSH concentration to the levels observed in non-stressed cells (C). Quercetin derivatives and chlorogenic acid, the main components of the extract, have well documented in vitro antioxidant properties [ 35 ]. Furthermore, their antidiabetic activity has been confirmed in numerous in vivo studies.…”
Section: Resultsmentioning
confidence: 99%
“…Possibly, not one chemical compound is responsible for inhibition of C. parvum but rather a synergistic mixture of several substances [ 41 ]. Plant metabolites have evolved to possess certain activities depending on the reaction milieu, as described for the pro- and anti-oxidant activities of flavonoids [ 10 12 ]. Easily oxidisable compounds, like many anti-oxidants, tend to form radicals that may interfere with essential parasite enzymes; this might represent one conceivable mode of action against C. parvum for a material rich in anti-oxidants like OEE.…”
Section: Discussionmentioning
confidence: 99%